2009
DOI: 10.1097/fbp.0b013e32832ec57e
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular signal-regulated kinase activation in the amygdala mediates elevated plus maze behavior during opioid withdrawal

Abstract: This study examined whether activation of extracellular signal-regulated kinase (ERK) contributes to the increased open-arm time observed in the elevated plus maze (EPM) during opioid withdrawal. We applied SL327, a selective ERK kinase (MEK) inhibitor, to specific limbic areas and examined the effect on EPM behaviors of controls and during naloxone-precipitated morphine withdrawal. We next confirmed that ERK activation increased in limbic areas of mice undergoing naloxone-precipitated morphine withdrawal. Dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 46 publications
2
11
0
Order By: Relevance
“…In the current report, we showed that mice undergoing NAL‐precipitated MOR withdrawal exhibit an increase in the time spent and entries to the open‐arms of the EPM in accordance with previous studies (Hodgson et al, ; Hofford et al, ; Lipták et al, ). The interpretation of these results is quite controversial but, a recent report by Lipták et al, () has shown that mice undergoing NAL‐precipitated MOR withdrawal spent significantly more time and traveled significantly more distance in the center of the open field compared to the control mice confirming the results observed in the EPM.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the current report, we showed that mice undergoing NAL‐precipitated MOR withdrawal exhibit an increase in the time spent and entries to the open‐arms of the EPM in accordance with previous studies (Hodgson et al, ; Hofford et al, ; Lipták et al, ). The interpretation of these results is quite controversial but, a recent report by Lipták et al, () has shown that mice undergoing NAL‐precipitated MOR withdrawal spent significantly more time and traveled significantly more distance in the center of the open field compared to the control mice confirming the results observed in the EPM.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, the EPM behaviors of withdrawn mice could indicate an increased motivation to scape that induces exploration and/or risk‐taking behaviors similar to the behaviors observed in addicts (Hodgson et al, ). Interestingly, all studies performed in mice show an anxiolitic‐like behavior during naloxone‐precipitated morphine withdrawal in the EPM test (Buckman et al, 2008; Hofford et al, ; Lipták et al, ). However, studies performed in rats (Zhang et al, 2008) show an anxiety‐like behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ERK 1/2 inhibitors can attenuate the analgesic effect evoked by morphine [29,30] and block the increased open arm-time after morphine withdrawal on EPM [31]. There is no data about the effect of obestatin on ERK 1/2 pathway in the central nervous system after in vivo treatment, but obestatin might exert its effect on mild morphine withdrawal and analgesia via regulation of ERK 1/2 pathway.…”
Section: Discussionmentioning
confidence: 91%
“…Recently, reports have implicated ERK 1/2 signal transduction in morphine reward and plasticity including place preference and psychomotor sensitization (134; 135) . ERK 1/2 activity in the amygdala was also found to mediate anxiety-like behaviors during morphine withdrawal (136) . Together, these reports strongly support the concept that ERK 1/2 signaling is an essential mediator of μ-opioid-induced plasticity in the brain and spinal cord.…”
Section: Opioid Signaling and Behaviormentioning
confidence: 99%